2012
DOI: 10.1111/j.1465-7295.2012.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

The Duration of Firm‐destination Export Relationships: Evidence From Spain, 1997–2006

Abstract: This article uses survival analysis to investigate the duration of Spanish firms' trade relationships by destination over 1997–2006. Whereas firm export status is highly persistent, firms' destination portfolio is very dynamic: a typical firm‐country exporting relationship has a median duration of 2 years. Yet, if a firm manages to export to a country beyond 2 years the risk of exiting that market sharply falls afterwards. The results indicate that not only firm heterogeneity but also destination heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 31 publications
9
39
1
2
Order By: Relevance
“…industry, year and cohort) are fully controlled for in this estimation, this negative effect of export duration on the probability of exiting from export markets implies that firms are less likely to stop exporting the longer they continue exporting, which is consistent with the theoretical predictions mentioned in Section 2. Second, firms with higher TFP tend to survive in export markets for a longer period, which is consistent with the findings of previous studies, such as those by Békés and Muraközy (), Görg et al () and Esteve‐Pérez et al (). Third, as expected, firms with a high RDRATIO or ADVRATIO tend to survive in export markets longer.…”
Section: Empirical Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…industry, year and cohort) are fully controlled for in this estimation, this negative effect of export duration on the probability of exiting from export markets implies that firms are less likely to stop exporting the longer they continue exporting, which is consistent with the theoretical predictions mentioned in Section 2. Second, firms with higher TFP tend to survive in export markets for a longer period, which is consistent with the findings of previous studies, such as those by Békés and Muraközy (), Görg et al () and Esteve‐Pérez et al (). Third, as expected, firms with a high RDRATIO or ADVRATIO tend to survive in export markets longer.…”
Section: Empirical Analysissupporting
confidence: 90%
“…Although there have recently been a number of studies focusing on firm‐level characteristics in explaining export duration (e.g. Békés and Muraközy, ; Esteve‐Pérez et al, ; Gullstrand and Persson, ), such firm‐level empirical evidence is still comparatively scarce. This means that our knowledge on firm‐level trade patterns (in particular temporary or “on–off” exporting by firms) is still limited and that it is not sufficiently clear what kind of firms become “always exporters”.…”
Section: Introductionmentioning
confidence: 99%
“…First, our long panel data set allows us to conduct a survival analysis-type study on the status of exporting firms. Very few studies have examined the determinants of survival in export markets through hazard estimation using firm-level data, with the exception of Esteve-Pérez et al (2013). This is another important dimension discussed in the theoretical international trade literature (e.g., Schröder and Sørensen 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the observation by Dunn and Bradstreet (2011), who state that just half of all the new ventures will still be in business after 10 years and that the risk of export closure is highest during the firm's first 5 years of operations. In a pooled regression analysis, Esteve-Pérez et al (2013) also found out that trading relationships by younger firms (up to 10 years old) last longer than those of older firms. Relationships are a lifeline to venture survival.…”
Section: Literature Review and The Set Hypothesismentioning
confidence: 92%